Are Countries Investments in Tertiary Education Making a Difference? - Benoît, Millot (World Bank, Washington, DC, 2014)
Although the relationship between education spending and outcomes has been the topic of a fairly rich body of research at the primary and secondary levels and has been found fairly ambiguous it has been poorly documented at the tertiary level, despite ever rising expenditures at this level. This paper is exploring the impact of various measures of spending on a range of outcomes of tertiary education, using cross-country comparisons. It finds that public expenditures are only loosely linked with outcomes in terms of access and participation, but that they are positively associated with proxies of quality. Private expenditures appear to have no impact on either quantity or quality. This exploratory research shows very different patterns for the group of high-income countries and less developed countries. Data allowing, it also sheds a special light on the South Asia Region, where patterns largely echoes the situation of the low income countries.